The spectres of Andrés Bello in the Chilean academy - Fierro, Francisco Durán del (Cinta de moebio, 2024)
In Chile, the contemporary form of academic life is irreducible to neoliberalism. There are past experiences and discourses that continue to disrupt the daily routine, dynamics, intensity, and rhythm of academics. They manifest as various epistemological, ethical, institutional, technical, and political mechanisms that produce innumerable images, meanings, and practices. These experiences conflict with the affects and material realities of the neoliberalism. The entanglement of these experiences from the past and present is conflicting, as they attempt to ignore or repress each other. In this respect, this paper addresses the following question: what is the model of academic behaviour that was established during the post-independence period in the Chilean university system? To answer this question, I explore Andres Bello's texts concerning university and academic life. The conclusion is that Bello established a specific model of academic behaviour that, with some later modifications, reconfigurations, and contradictions, returns to the present. Bello's influence today can be seen through spectres that enable and limit new possibilities for expanding academic critique within and across scholarly settings.